Immunotherapy and Tyrosine Kinase Inhibitor as a Bridge to Surgery for Clear Cell Renal Cell Carcinoma Metastases to the Thyroid: A Case Report and Literature Review - Robert Bränström; Jan Zedenius; Ivan Shabo; Magnus Lindskog; C. Christofer Juhlin (Case Reports in Oncology, 2024)
Introduction: Clear cell renal cell carcinoma (ccRCC), the most common type of kidney cancer in adults, presents significant challenges owing to its resistance to conventional therapies. Standard treatment primarily revolves around surgical methods, particularly nephrectomy, which is critical for managing localized diseases. Despite recent advancements, the metastatic potential of ccRCC necessitates ongoing vigilance in postoperative monitoring to manage and detect disease recurrence. Recent shifts in treatment paradigms, especially with the integration of molecular patterns in ccRCC, have enabled the development of targeted therapies. Immune checkpoint and tyrosine kinase inhibitors (TKIs) have become central to managing metastatic ccRCC, offering new hope through improved survival outcomes. Recent studies have corroborated this by demonstrating the benefits of combining these therapies. Case Presentation: This report discusses a case study of a patient with high-grade ccRCC and thyroid metastases initially deemed non-resectable. The combination of immunotherapy and TKIs reduced tumor size, transforming the thyroid metastasis to a resectable state. Conclusion: This case highlights significant advancements in treatment approaches and the critical in the management of ccRCC, underscoring the necessity for continuous adaptation of clinical practices to incorporate new therapeutic developments.